Orientation towards social domination, reality and dimensions (Journal of the College of Basic Education, 2023)
When the field of social psychology interacts with the field of political psychology, it resultsA very dangerous socio-political phenomenon called the trend towards social domination, whichIt is the basis for many psychological and social phenomena such as injustice, persecution and discriminationAnd intolerance in all its forms and types, so the current research aimed to verify the existence of thisOrientation in a society that has suffered from injustice and persecution for thousands of years, and the reality of this orientation, which isthe applied side of the research; In addition to identifying the most important psychological and social dimensions of thisOrientation, which represents the theoretical side of the research; Therefore, it required the construction of a measure of orientation towards dominancesocial and measuring this phenomenon, which has already proven its existence in a realistic way in society.